Divergence of the diapause transcriptome in apple maggot flies: winter regulation and post-winter transcriptional repression - Meyers, P. J.; Powell, T. H. Q.; Walden, K. K. O.; Schieferecke, Adam J.; Feder, J. L.; Hahn, D. A.; Robertson, H. M.; Berlocher, S. H.; Ragland, Gregory J. (My University, 2016)
The duration of dormancy regulates seasonal timing in many organisms and may be modulated by day length and temperature. Though photoperiodic modulation has been well studied, temperature modulation of dormancy has received less attention. Here, we leverage genetic variation in diapause in the apple maggot fly, Rhagoletis pomonella, to test whether gene expression during winter or following spring warming regulates diapause duration. We used RNAseq to compare transcript abundance during and after simulated winter between an apple-infesting population and a hawthorn-infesting population where the apple population ends pupal diapause earlier than the hawthorn-infesting population. Marked differences in transcription between the two populations during winter suggests that the 'early' apple population is developmentally advanced compared with the 'late' hawthorn population prior to spring warming, with transcripts participating in growth and developmental processes relatively up-regulated in apple pupae during the winter cold period. Thus, regulatory differences during winter ultimately drive phenological differences that manifest themselves in the following summer. Expression and polymorphism analysis identify candidate genes in the Wnt and insulin signaling pathways that contribute to population differences in seasonality. Both populations remained in diapause and displayed a pattern of up-and then down-regulation (or vice versa) of growth-related transcripts following warming, consistent with transcriptional repression. The ability to repress growth stimulated by permissive temperatures is likely critical to avoid mismatched phenology and excessive metabolic demand. Compared with diapause studies in other insects, our results suggest some overlap in candidate genes/pathways, though the timing and direction of changes in transcription are likely species specific.
Citation: Meyers, P. J., Powell, T. H. Q., Walden, K. K. O., Schieferecke, A. J., Feder, J. L., Hahn, D. A., . . . Ragland, G. J. (2016). Divergence of the diapause transcriptome in apple maggot flies: winter regulation and post-winter transcriptional repression. Journal of Experimental Biology, 219(17), 2613-2622. doi:10.1242/jeb.140566
Keywords: Diapause; Phenology; Overwintering; Gene Expression; Rhagoletis; Pitcher-Plant Mosquito